Ideal tensile strength and shear strength of ZrO2(111)/Ni(111) ceramic-metal Interface: A first principle study. (15th December 2016) - Guo, Xingye; Zhang, Yi; Jung, Yeon-Gil; Li, Li; Knapp, James; Zhang, Jing
Abstract: The ideal mechanical strengths of ZrO2 (111)/Ni(111) ceramic-metal (C-M) interface are calculated through simulated tensile and shear deformations using the first principles calculations. The structures of ZrO2 (111)/Ni(111) interfaces with 1- and 3-layer Ni thicknesses are optimized and the mechanical properties are investigated. For tensile deformation in [111] direction, the Young's moduli of the 1-layer Ni and 3-layer Ni M-C models are 139.9 GPa and 60.2 GPa, respectively; and ultimate tensile strengths are 11.6 GPa and 7.9 GPa, respectively. For shear deformation in 111 〈110〉 system, the shear moduli of the 1-layer Ni and 3-layer Ni M-C models are 43.9 GPa and 30.4 GPa, respectively; and ultimate shear strengths are 7.0 GPa and 3.0 GPa, respectively. For shear deformation in 111 〈11 2 − 〉 system, the shear moduli of the 1-layer Ni and 3-layer Ni M-C models are 30.9 GPa and 17.3 GPa, respectively; and ultimate shear strengths are 6.0 GPa and 1.8 GPa, respectively. Overall, 1-layer Ni C-M interface models have better mechanical properties than those of 3-layer models. The observed strengths are explained by using charge distribution, electron localization function, and Bader charge transfer analyses. The results are important for designing robust thermal barrier coating through optimizing bond coat thickness. Graphic abstract: Highlights: Ideal tensile and shear strengths of ZrO2/Ni interface are calculated using DFT. Stress-strain curves of interfaces in tensile and shear deformations are calculated. 1-layer Ni interface models have higher mechanical strengths than 3-layer models. Charge density and Bader charge analyses are conducted to explain the strengths.